FUNFING OF CORPORATIONS THROUGH AN IPO ON THE STOCK MARKET: BENEFITS AND LIMITATIONS - MOZGOVYY, Oleg; YURKEVYCH, Oksana; SUBOCHEV, Alexey (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article conducts a comprehensive analysis of corporate financing through an Initial Public Offering (IPO) on the stock market, focusing on the benefits and limitations of this strategic step. The study is structured to provide a holistic view, beginning with the legal definition of an IPO according to Ukrainian legislation, which synthesizes norms from key regulatory acts governing capital markets, joint-stock companies, and information disclosure. The authors place the Ukrainian IPO market in a historical context, noting its underdevelopment compared to Western Europe and identifying key reasons for this, including the legacy of voucher privatization, lack of a robust institutional investor base, currency instability, and weak protection of minority shareholder rights.The core of the article is a detailed examination of the multi-stage IPO process, which typically lasts from 6 to 12 months. The authors meticulously describe each critical phase: the selection of an underwriter (investment bank), conducting comprehensive due diligence, preparing the issuance prospectus, marketing and the road show, and the final placement and listing on the stock exchange. This structured process is presented as essential for ensuring transparency, protecting investor rights, and ensuring a successful market debut. A significant portion of the research is dedicated to a strategic analysis of the advantages and disadvantages. The benefits extend beyond direct financial enrichment and include non-financial strategic advantages such as enhanced brand prestige and trust among clients and suppliers, increased liquidity for founders and early investors, and the attraction of strategic partners. Furthermore, the transition to a public company necessitates improved corporate governance standards, including the adoption of International Financial Reporting Standards (IFRS) and transparent procedures, which ultimately increase investor confidence and the company's market valuation. Conversely, the article provides a thorough analysis of the substantial limitations and risks. These include high direct costs (underwriter commissions, legal and auditing fees) and significant indirect costs, primarily the diversion of management's attention from operational activities. Major risks also involve the potential loss of control and confidentiality due to the dilution of founders’ shares and mandatory disclosure of sensitive financial and operational information, as well as increased vulnerability to market fluctuations and legal liability. The conclusion emphasizes that an IPO is a strategically justified choice only for mature companies with a proven business model, a clear strategy for using the raised capital, and a readiness for public scrutiny. The decision must be based on a balanced analysis where the long-term benefits of accessing capital, enhancing status, and improving management outweigh the associated costs, risks, and loss of privacy. The success of an IPO is also critically dependent on favourable market conditions.
Keywords: IPO; stock market; corporate finance; corporate governance; public companies; international investments; portfolio investment; IPO risks; strategic investors; securities